Field evidence of CO2 sequestration by mineral carbonation in ultramafic milling wastes, Thetford Mines, Canada. (April 2016) - Lechat, Karl; Lemieux, Jean-Michel; Molson, John; Beaudoin, Georges; Hébert, Réjean
Highlights: Field observations of natural/passive mineral carbonation in milling wastes. Major evidences are low CO2 concentrations and the presence of hydromagnesite. The estimated amount of sequestrated CO2 is 4 kg/m 3 /year. A conceptual model for mineral carbonation in ultramafic milling wastes is proposed. Abstract: Two experimental small-scale cells have been constructed in the field to better understand passive mineral carbonation under natural atmospheric conditions in the ultramafic milling wastes of Thetford Mines (Québec, Canada). The magnesium-rich milling wastes mainly consist of poorly sorted grains and fibers of lizardite and chrysotile, with smaller amounts of antigorite, brucite and magnetite. These wastes could serve as significant and long-term CO2 sinks but the mechanisms and rates of mineral carbonation are not well understood. In this paper, the design of the experimental cells along with observations on gas composition, gas pressure, soil temperature, volumetric water content and mineral composition are presented with the objective to better understand the mineral carbonation processes under natural conditions and to propose a conceptual model for mineral carbonation at the field cell scale. Low CO2 concentrations (5–50 ppm) measured in the experimental cells and the presence of hydromagnesite suggest that natural and passive mineral carbonation is a significant process occurring in the magnesium-rich wastes (4 kg/m 3 /year of sequestrated CO2 ). In the proposed conceptual model, atmospheric CO2 (∼400 ppm) dissolves in the hygroscopic water of the piles, where weathering of magnesium silicates forms magnesium carbonates. Water saturation in the cells is relatively stable over time and varies between 0.4 and 0.65, which is higher than optimal saturation values proposed in the literature, reducing CO2 transport in the unsaturated zone. Gas-phase CO2 concentrations along with gas flow rate measurements in the cells suggest that the reaction is most active close to the surface and that diffusion of CO2 is the dominant transport mechanism in the wastes. Although the carbonation reaction is exothermic, no evidence of thermal convection has been observed in the experimental cells. This conceptual model will serve to support a reactive transport model in order to quantify and optimize the amount of CO2 that can be captured in chrysotile milling waste piles.